On n-absorbing δ -primary ideals - (:unkn) unknown (My University, 2018)
Let R be a commutative ring with nonzero identity and n be a positive integer. In this paper, we studythe concepts of n-absorbing δ -primary ideals and weakly n-absorbing δ -primary ideals, which are the generalizationsof δ -primary ideals and weakly δ -primary ideals, respectively. We introduce the concepts of n-absorbing δ -primaryideals and weakly n-absorbing δ -primary ideals. Moreover, we give many properties of these new types of ideals andinvestigate the relations between these structures.
Keywords: Matematik